2018
DOI: 10.1007/s11626-018-0232-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-148a-3p promotes rabbit preadipocyte differentiation by targeting PTEN

Abstract: Although emerging data support crucial roles for microRNAs (miRNAs) during adipogenesis, the detailed mechanisms remain largely unknown. In this study, it was shown that in rabbits, levels of miR-148a-3p not only increased in white adipose tissue during early stages of growth but also during in vitro cultured preadipocyte differentiation. Furthermore, overexpression of miR-148a-3p significantly upregulated the mRNA levels of PPARγ, C/EBPα, and FABP4, as well as the protein levels of PPARγ, as indicated by qPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…Similar results were also carried out in gastric cancer and HCC and miR‐148a was found up‐regulated in glioblastoma and chordomas . In our study, we figured c‐Jun as the target protein of miR‐148a, and it was the first time to combine miR‐148a and c‐Jun .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar results were also carried out in gastric cancer and HCC and miR‐148a was found up‐regulated in glioblastoma and chordomas . In our study, we figured c‐Jun as the target protein of miR‐148a, and it was the first time to combine miR‐148a and c‐Jun .…”
Section: Discussionsupporting
confidence: 87%
“…Lifers revealed miR‐148a, down‐regulated in human pancreatic ductal adenocarcinomas, regulated cell survival via CDC25B, a conserved dual specificity phosphatase which was significant in appropriate cell cycle . Similar results were also carried out in gastric cancer and HCC and miR‐148a was found up‐regulated in glioblastoma and chordomas .…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…For example, Wang et al 24 confirmed that TGFBR1 and TGFBR2 are direct targets of miR-204 in fetal human retinal pigment epithelium using luciferase reporter assays. 31 It has also been previously reported that miR-204 is involved in cell proliferation and apoptosis, as Xin et al 32 found that this miRNA suppresses glioblastoma cell proliferation, migration, and invasion by targeting CYP27A1. Flores-Perez et al 26 found that miR-204 regulates tumor angiogenesis by targeting ANGPT1 and TGFBR2 in breast cancer.…”
Section: Discussionmentioning
confidence: 79%